FTIR spectroscopic analysis of protein/carrier interactions in novel protein delivery systems - (:unkn) unknown (My University, 2002)
The objective of this work was to investigate the binding of calcitonin to complexation hydrogels composed of poly(methacrylic acid) (PMAA) grafted with poly(ethylene glycol) (PEG), henceforth designated as P(MAA-g-EG). This was done to investigate the complexation and decomplexation of these hydrogels in buffered solutions, using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy. P(MAA-g-EG) hydrogel films were prepared by free radical solution polymerization using the spin coating method. The ensuingfilms were tested directly on Ge crystals. Carbonyl ion peaks were used to identify protein/P(MAA-g-EG) binding due to electrostatic and hydrogen bonding interactions between the complexation hydrogel and the protein. As the pH values increased, the asymmetric and symmetric stretching vibrations appeared in the spectra identifying the C(=0)-O functional group. In addition, the binding of calcium to P(MAA-g-EG) hydrogels was investigated to elucidate the complexation mechanism.
Keywords: ATR-FTIR spectroscopy; Calcitonin; Calcium; Hydrogel; Poly(ethylene glycol); Poly(methacrylic acid)